2012
DOI: 10.1104/pp.112.199067
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Organ Boundaries Domain Transcription Factor LBD20 Functions in Fusarium Wilt Susceptibility and Jasmonate Signaling in Arabidopsis  

Abstract: The LATERAL ORGAN BOUNDARIES (LOB) DOMAIN (LBD) gene family encodes plant-specific transcriptional regulators functioning in organ development. In a screen of Arabidopsis (Arabidopsis thaliana) sequence-indexed transferred DNA insertion mutants, we found disruption of the LOB DOMAIN-CONTAINING PROTEIN20 (LBD20) gene led to increased resistance to the root-infecting vascular wilt pathogen Fusarium oxysporum. In wild-type plants, LBD20 transcripts were barely detectable in leaves but abundant in roots, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 63 publications
(120 reference statements)
4
92
0
Order By: Relevance
“…One member of the LOB domain family, AtLBD18, was reported to bind with the promoter of EXPANSIN14, a gene involved in cell wall loosening (38). Recently, the Arabidopsis LOB family protein LBD20 was proposed as a host S gene for the fungal pathogen Fusarium oxysporum, functioning in the jasmonate signaling pathway (39). AtLBD20 was induced by F. oxysporum, and the overexpression of LBD20 was correlated with increased susceptibility to infection and reduced the expression of JA-regulated genes VEGETATIVE STORAGE PROTEIN2 (VSP2) and THI-ONIN2.1 (Thi2.1).…”
Section: Discussionmentioning
confidence: 99%
“…One member of the LOB domain family, AtLBD18, was reported to bind with the promoter of EXPANSIN14, a gene involved in cell wall loosening (38). Recently, the Arabidopsis LOB family protein LBD20 was proposed as a host S gene for the fungal pathogen Fusarium oxysporum, functioning in the jasmonate signaling pathway (39). AtLBD20 was induced by F. oxysporum, and the overexpression of LBD20 was correlated with increased susceptibility to infection and reduced the expression of JA-regulated genes VEGETATIVE STORAGE PROTEIN2 (VSP2) and THI-ONIN2.1 (Thi2.1).…”
Section: Discussionmentioning
confidence: 99%
“…Thatcher et al (2009), have demonstrated JA perception mutant coronatine insensitive 1 (coi1), but not JA biosynthesis mutants, which exhibited a high level of resistance to wilt disease caused by F. oxysporum in Arabidopsis Kidd et al (2011) thaliana. Recently a novel transcription factor, LBD20 (Lateral Organ Boundaries Domain) gene which on its disruption led to increased resistance in Arabidopsis to Fox was found and this suggests that LBD20 is a Fusarium susceptibility gene that appears to regulate components of JA-signaling downstream of COI1 and MYC2 transcription factors (Thatcher et al 2012a). JA signaling has a dichotomous involvement in the Arabidopsis interaction with F. graminearum, contributing to the attenuation of SA signaling during the early stages of infection and promotion of defense against F. graminearum during later stages of infection (Makandar et al 2010).…”
Section: Salicylic Acid (Sa) Jasmonic Acid (Ja) and Ethylene (Et)mentioning
confidence: 99%
“…In addition to LBD20 expression being induced by F. oxysporum infection, we also found its expression was responsive to the defense signaling hormone JA. 15 In GENEVESTIGATOR, we only found LBD genes differentially expressed greater than 1.5-fold from controls to be repressed by JA treatment (data not shown). Again, the class II LBD genes (LBD37, 38, 39 and 41) were most responsive.…”
mentioning
confidence: 99%
“…14, [16][17][18] We now demonstrate a role for LBD20 in JA-signaling where it functions downstream of COI1 and MYC2, 15 respectively part of the JA receptor complex and a key downstream transcriptional regulator of JA signaling (for a review see ref. 19).…”
mentioning
confidence: 99%
See 1 more Smart Citation